First trimester combined screening test in pregnancies derived from blastocyst transfer. (March 2016) - Cavoretto, Paolo; Dallagiovanna, Chiara; Viganò, Paola; Somigliana, Edgardo; Persico, Nicola; Papaleo, Enrico; Faulisi, Sonia; Candiani, Massimo
Abstract: Objective: To investigate whether first trimester combined screening for major fetal trisomies is influenced by assisted reproduction techniques from blastocyst transfer, with or without cryopreservation. Study design: retrospective case-control analysis involving 298 singleton pregnancies with euploid fetuses recruited between 2012 and 2014. Forty-seven women conceived with fresh blastocysts from in vitro fertilization cycles (fresh-blasto), 51 with frozen–thawed blastocysts (frozen-blasto) and 200 were natural conceptions (controls). All cases underwent ultrasound assessment at 11 +0 –13 +6 weeks with measurements of crown rump length, nuchal translucency, free β-hCG and PAPP-A concentrations. The outcome of pregnancy was recorded (gestational age at birth, birth weight, obstetric complications). Results: Baseline characteristics and pregnancy outcomes did not differ substantially among the study groups. The median delta nuchal translucency was significantly higher both in frozen-blasto group (median: 0.27 mm; Interquartile Range [IQR]: 0.02–0.44; p < 0.001) and in fresh-blasto group (median: 0.17 mm; IQR: 0.04–0.39; p = 0.014) as compared to control group (median: 0.06 mm; IQR: −0.08 to 0.20), whereas it was not different in the frozen-blasto compared to the fresh-blasto group. The median free β-hCG multiples of the median (MoMs) was significantly higher both in frozen-blasto group (median 1.15; IQR 0.83–2.11; p = 0.001) and in fresh-blasto group (median 0.95; IQR 0.52–1.48; p = 0.001) as compared to control group (median 0.99; IQR 0.57–1.26), and it was also higher in frozen-blasto group compared to fresh-blasto group ( p < 0.001). The three groups showed no significant differences in the median PAPP-A MoMs. The median delta crown rump length was also not significantly different among the three groups. Conclusions: in assisted reproduction technique pregnancies from blastocyst transfer, with or without cryopreservation, both the nuchal translucency measurement and free β-hCG concentration are higher as compared to spontaneous conceptions, whereas PAPP-A does not show any significant difference. These features are apparently unrelated to the outcome of pregnancy and may be due to alterations or delays in embryogenesis or placentation with potential relevance for the screening test performance.